Translation, Validation, and Cultural Adaptation of The Barthel Index Questionnaire in Patients with First-Time Ischemic Stroke - Salbila Nurngazizath Sudirman; Ilham Alifiar; Nur Rahayuningsih (PT Pubsains Nur Cendekia, 2026)
Background: Ischemic stroke is one of the leading causes of long-term functional disability, requiring accurate assessment of a patient’s ability to perform activities of daily living. The Barthel Index is a widely used instrument for evaluating functional independence. However, culturally adapted version in both Indonesian and Sundanese languages have not yet been developed for stroke patients in the Tasikmalaya region. Aim: This study aimed to conduct the translation, cultural adaptation, and validate of the Barthel Index questionnaire in patients experiencing their first ischemic stroke. Methods: An observational study with a cross-sectional design was conducted involving 40 respondents at KHZ Mustofa Hospital, Tasikmalaya. The translation process employed a forward-backward translation method by professional translators, followed by expert reviews and cultural adaptation through panel discussions. Validity testing was performed using criterion validity and construct validity based on Structural Equation Modeling (SEM), while reliability testing used Cronbach's Alpha. Results: The results showed path coefficient values ≥ 0.5 and t-statistics > 1.96, indicating strong construct validity. Cronbach's Alpha was 0.870, reflecting high internal consistency. The model also demonstrated acceptable Average Variance Extracted (AVE ≥ 0.5) and Composite Reliability (CR ≥ 0.7). Conclusion: These findings confirm that the Indonesian and Sundanese versions of the Barthel Index are valid and reliable instrument for assessing the functional independence of ischemic stroke patients the local cultural context. This instrument is expected to support clinical decision-making and further research in hospital pharmacy and rehabilitation settings.